2019
DOI: 10.1037/sah0000121
|View full text |Cite
|
Sign up to set email alerts
|

A modified framework for identifying stigma: News coverage of persons with mental illness killed by police.

Abstract: This paper examines the types of stigmatizing language and frames present in news reports about persons with mental illness killed by police. A sample of 301 online news reports was content analyzed, of which 132 reports contributed to 231 examples of stigmatizing language or frames. Analysis indicates that the construction of stigma in these news reports does not fully adhere to existing frameworks for identifying stigmatization. Stigmatization that is implicit, and often seemingly innocuous, is almost three … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…A fruitful starting point may be to investigate the types of messages that are conveyed about self-injury at a broad societal level, given that stereotypes are socially learned scripts that inform prejudice and discrimination (Corrigan, 2000). Mass media can be a vehicle for the communication of stereotypes (Frankham, 2019) and present an important avenue for investigating messaging about NSSI. Exploring how NSSI is portrayed by news and other popular media may give important insights into the development of public NSSI stigma.…”
Section: Future Directionsmentioning
confidence: 99%
“…A fruitful starting point may be to investigate the types of messages that are conveyed about self-injury at a broad societal level, given that stereotypes are socially learned scripts that inform prejudice and discrimination (Corrigan, 2000). Mass media can be a vehicle for the communication of stereotypes (Frankham, 2019) and present an important avenue for investigating messaging about NSSI. Exploring how NSSI is portrayed by news and other popular media may give important insights into the development of public NSSI stigma.…”
Section: Future Directionsmentioning
confidence: 99%
“…In New Zealand, the number of individuals seen for mental health care grew by approximately 40% in the years between 2010/2011 and 2019/2020, putting the health system under considerable pressure (Elliott, 2017;Office of the Health and Disability Commissioner, 2018;Patterson et al, 2018). He Ara Oranga, the 2018 Mental Health and Addiction Inquiry Report commissioned by the New Perhaps as a result of this pressure on health services, mental health-related calls to emergency services have also seen steep increases, in line with international trends (Frankham, 2019). This is when police or ambulance services are contacted through an emergency number such as 911 or 000 (111 in New Zealand) to respond urgently to a mental health crisis.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, at the level of exemplars, research has shown that the type of presentation (in terms of framing as well as the exemplars' characteristics) influences (de-)stigmatising effects in the context of exemplification (e.g., Baer et al, 2015;Frankham, 2019;Gwarjanski & Parrott, 2018;McGinty et al, 2014;Wahl, 1996;Wright et al, 2012). For example, Gwarjanski & Parrott (2018) found that the media holds stigma frames (i.e., the communication of stereotypes) as well as stigma-challenge frames (i.e., the contradiction of stereotypes) about schizophrenia.…”
Section: The Role Of Exemplification For the (De-)stigmatisation Of Mental Illnessmentioning
confidence: 99%
“…However, it still mostly portrays mental illness in a negative fashion and maintains the public's overall negative view on mental illness through the overuse and generalisation of labels, such as depression, to the facilitation of stereotypes (e.g., violent and suicidal: Wang, 2020), and negative framing. In addition, it continues to use pejorative language in association with mental illness (e.g., Baer et al, 2015;Gwarjanski & Parrott, 2018;McGinty et al, 2014;Frankham, 2019).…”
Section: The Role Of Exemplification For the (De-)stigmatisation Of Mental Illnessmentioning
confidence: 99%